A Case Study on Regenerating Informal Settlements in Cairo using Affordable and Adaptable Building System. (2017) - Hu, Rongbo; Follini, Camilla; Pan, Wen; Linner, Thomas; Bock, Thomas
Abstract: This paper is a scientific review of the results from research project A 2 L-Mobilius, which is an ongoing research project partly funded by the German Federal Ministry of Education and Research (BMBF). Today the process of urbanization has reached an unprecedented level. Most of the rapid urbanization phenomena happen in developing countries, triggering a series of social, economic, and environmental challenges as well as opportunities. In particular, nearly two thirds of Greater Cairo Region's population are living in informal urban settlements, and the number is expected to continuously increase, which causes a series of issues such as overpopulation, land shortage, high unemployment rate, lack of adequate infrastructures, and environmental challenges. As a result, in the foreseeable future, the situation will be more problematic if no innovative measures are taken. Based on A 2 L-Mobilius, the goal of this paper is to present an integrated solution to improve the living condition of local residents and to catalyze the vitality of local community. With regard to the research methods, a small housing unit in Cairo's informal area is chosen as the object of the case study. Accordingly, field trip study by Egyptian partners is conducted in order to better understand the housing's condition as well as its surroundings. Based on the case study findings as well as the Open Building concept, the results consist of an Affordable and Adaptable Building System (A 2 BS) and a cluster of Decentralized Processing Units (DPUs), which generate key elements to improve energy efficiency, mobility, and life-work patterns. Furthermore, specifications and technological details of the proposed system will be presented in this paper. In conclusion, this case study provides a valuable model for further research on regenerating informal urban settlements.